PERTUMBUHAN BEBERAPA KULTIVAR PADI GOGO LOKAL (Oryza satifa L.) PADA BERBAGAI INTERVAL WAKTU PENYIRAMAN - Rabani, Nur Muhamad; Ete, Andi (Fakultas Pertanian, Universitas Tadulako, 2024)
This study aimed to evaluate the drought tolerance of different local upland rice cultivars under various watering intervals. The research was conducted at the Greenhouse of Plant Breeding, Faculty of Agriculture, Tadulako University, Palu, from June to August 2020. A two-factorial completely randomized design was used. The first factor was the rice cultivar, comprising three types: Pulu Tau Leru, Jahara, and Uva Buya. The second factor was the watering interval, with five level watering: daily (P1), every other day (P2), every two days (P3), every three days (P4), and every four days (P5). This resulted in 15 treatment combinations, each replicated four times, totaling 60 experimental units. Observed parameters included plant height, leaf length, leaf curl, and number of tillers. The results indicated that the growth of the different local upland rice cultivars was significantly affected by the watering intervals across all observed parameters.